Description of Cryptosporidium ornithophilus n. sp. (Apicomplexa: Cryptosporidiidae) in farmed ostriches - Holubová, Nikola; Tůmová, Lenka; Sak, Bohumil; Hejzlarová, Adéla; Konečný, Roman; McEvoy, John; Kváč, Martin (Parasites & vectors, 2020)
BACKGROUND: Avian cryptosporidiosis is a common parasitic disease that is caused by five species, which are well characterised at the molecular and biological level, and more than 18 genotypes for which we have limited information. In this study, we determined the occurrence and molecular characteristics of Cryptosporidium spp. in farmed ostriches in the Czech Republic. METHODS: The occurrence and genetic identity of Cryptosporidium spp. were analysed by microscopy and PCR/sequencing of the small subunit rRNA, actin, HSP70 and gp60 genes. Cryptosporidium avian genotype II was examined from naturally and experimentally infected hosts and measured using differential interference contrast. The localisation of the life-cycle stages was studied by electron microscopy and histologically. Infectivity of Cryptosporidium avian genotype II for cockatiels (Nymphicus hollandicus (Kerr)), chickens (Gallus gallus f. domestica (L.)), geese (Anser anser f. domestica (L.)), SCID and BALB/c mice (Mus musculus L.) was verified. RESULTS: A total of 204 individual faecal samples were examined for Cryptosporidium spp. using differential staining and PCR/sequencing. Phylogenetic analysis of small subunit rRNA, actin, HSP70 and gp60 gene sequences showed the presence of Cryptosporidium avian genotype II (n = 7) and C. ubiquitum Fayer, Santín & Macarisin, 2010 IXa (n = 5). Only ostriches infected with Cryptosporidium avian genotype II shed oocysts that were detectable by microscopy. Oocysts were purified from a pooled sample of four birds, characterised morphometrically and used in experimental infections to determine biological characteristics. Oocysts of Cryptosporidium avian genotype II measure on average 6.13 × 5.15 μm, and are indistinguishable by size from C. baileyi Current, Upton & Haynes, 1986 and C. avium Holubová, Sak, Horčičková, Hlásková, Květoňová, Menchaca, McEvoy & Kváč, 2016. Cryptosporidium avian genotype II was experimentally infectious for geese, chickens and cockatiels, with a prepatent period of four, seven and eight days post-infection, respectively. The infection intensity ranged from 1000 to 16,000 oocysts per gram. None of the naturally or experimentally infected birds developed clinical signs in the present study. CONCLUSIONS: The molecular and biological characteristics of Cryptosporidium avian genotype II, described here, support the establishment of a new species, Cryptosporidium ornithophilus n. sp.
Keywords: Cryptosporidiosis; nemoci ptáků; Struthioniformes; Animals; ptáci; Cryptosporidium; Birds; Host Specificity; stadia vývoje; C. ubiquitum; Experimental infections; Occurrence; Genes, Protozoan; Animals, Domestic; PCR; Life Cycle Stages; Cryptosporidium ornithophilus n. sp.; Classification; klasifikace; Bird Diseases; kryptosporidióza; hostitelská specificita; zvířata; protozoální geny; fylogeneze; hospodářská zvířata; taxonomické DNA čárové kódování; Oocyst size; Phylogeny; DNA Barcoding, Taxonomic; Cryptosporidium avian genotype II